2015
DOI: 10.1002/ajmg.a.37255
|View full text |Cite
|
Sign up to set email alerts
|

Marfan syndrome patient experiences as ascertained through postings on social media sites

Abstract: Marfan syndrome (MS) is a connective tissue disorder that affects thousands of adolescents [Population Reference Bureau, 2013]. Some adolescent patients with MS may use social media to express their experiences and emotions, but little is known about what patients choose to share online. To investigate social media content related to Marfan syndrome we used search terms "Marfan syndrome" and "Marfans" on six different social media sites. The top five recent and popular posts for each site were collected and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(23 citation statements)
references
References 10 publications
1
22
0
Order By: Relevance
“…Kelleher et al reported fatigue and depression as common symptoms discussed on social media by MFS patients. 29 This data can be useful in raising awareness for clinicians caring for these patients and facilitate appropriate adjustment of patient care. The use of social media can also help provide unity in the community and may help individuals become more comfortable sharing their experiences with MFS, creating a safe environment for encouragement and support.…”
Section: Social Interactionmentioning
confidence: 99%
See 4 more Smart Citations
“…Kelleher et al reported fatigue and depression as common symptoms discussed on social media by MFS patients. 29 This data can be useful in raising awareness for clinicians caring for these patients and facilitate appropriate adjustment of patient care. The use of social media can also help provide unity in the community and may help individuals become more comfortable sharing their experiences with MFS, creating a safe environment for encouragement and support.…”
Section: Social Interactionmentioning
confidence: 99%
“…The use of social media can also help provide unity in the community and may help individuals become more comfortable sharing their experiences with MFS, creating a safe environment for encouragement and support. 29 Additionally, online self-management programs could be established for Schneider et al 7 (1990)…”
Section: Social Interactionmentioning
confidence: 99%
See 3 more Smart Citations